Quality Management of Certified Lecturers in The VUCA ERA (Etnographic Studies in UIN PROF. K.H.Saifuddin Zuhri Purwokerto) - islami, nisa nisa (IAIN Syekh Nurjati Cirebon, 2023)
This research is aimed at: (1) describe the quality management of certified lecturers to implement the Tridharma of Higher Education in UIN Prof. K.H. Saifuddin Zuhri Purwokerto; and (2) describe the new concept of quality management of certified lecturers in UIN Prof. K.H. Saifuddin Zuhri Purwokerto. This research is qualitative research with ethnographic methods. Data in this study were collected using interview, observation and documentation techniques. While data analysis techniques are carried out simultaneously when the data collection process is carried out. The results showed that the steps taken to improve the quality of prospective lecturers who will take the certification test include:: (1) Carry out higher education training activities for lecturers; (2) Conducting religious moderation seminars; (3) Conducting workshops on reporting Lecturer Workload (LBKD); (4) Collaborate with Research and Community Service Institutes to organize research methods workshops; (5) Collaborating with the Institute for Research and Community Service to organize community service workshops. (6) Carry out guidance and assessment of Qur'an literacy and practice of worship for lecturers. These six steps have implications for improving the quality of certified lecturers in the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era.